Best practices of halal supply chain in food & beverage department: a comparative study in selected hotels / Nor Amrina Dahlan - Dahlan, Nor Amrina (2020)
Nowadays, the Halal marketplace is emerging as one of the most lucrative and influential market arenas in the global business today. Clean and safe services are a few of the elements in Halal food that are being practiced worldwide. Malaysia is one of the countries with a high Muslim population. Food industry in Malaysia is mostly concerned about producing Halal food since Malaysia is one of the Muslim countries and has already built Halal Hub on their own. Halal food is needed by consumers in any places either in food premises or restaurants. In Malaysia, Halal certification is issued solely for kitchens and restaurants in hotel businesses. Currently, Halal food premises are certified only by competent authorities in Malaysia, which is the Malaysian Department of Islam Development or ' Jabatan Kemajuan Islam Malaysia' (JAKIM). This certification indicates that premises are already complying with the Halal standards and safe to be consumed by consumers. Jn addition, this study explored best practices of Halal supply chain in selected Halal certified hotels. Methodologically, this study utilized a qualitative approach, which included observation and exploration of past literature to identify the current practices of hotel industry in Malaysia. The findings of this study demonstrated the best practices and recommendations that are relevant and related with the food and beverage businesses specifically for the hotel industry. It is hoped that the findings from this study would provide knowledge on other aspects that need to be controlled by management and not only focusing on food preparation. Regular inspections are also needed to improve the food quality at food premises in the future.